2020
DOI: 10.7150/jca.34773
|View full text |Cite
|
Sign up to set email alerts
|

Genipin increases oxaliplatin-induced cell death through autophagy in gastric cancer

Abstract: Oxaliplatin is used for treatment in combination with many drugs. However, the survival rate is still low due to side effects and drug resistance. Therefore, the combination with natural products was required for increasing efficacy and reducing side effects. Genipin, a natural product derived from the Gardenia jasminoides, associated with anti-angiogenic, anti-proliferative, hypertension, inflammatory, and the Hedgehog pathway. It is not known that genipin increases the therapeutic effect of oxaliplatin in ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…4C and D). Some previous studies suggested that genipin can induce autophagy through the p53-DRAM signaling pathway in gastric cancer treatment or via the PI3K/AKT/mTOR signaling pathway in oral squamous cell carcinoma treatment [39,40]. Herein, genipin was also con rmed to induce autophagy, which may further be involved in regulating Tau phosphorylation.…”
Section: Discussionmentioning
confidence: 81%
“…4C and D). Some previous studies suggested that genipin can induce autophagy through the p53-DRAM signaling pathway in gastric cancer treatment or via the PI3K/AKT/mTOR signaling pathway in oral squamous cell carcinoma treatment [39,40]. Herein, genipin was also con rmed to induce autophagy, which may further be involved in regulating Tau phosphorylation.…”
Section: Discussionmentioning
confidence: 81%
“…Within core machinery, numerous autophagy genes including ULK1/2 , ATG2b , ATG4a/c , ATG7 , ATG10 and UVRAG are all bound by p53, which are directly involved in or regulate the composition of autophagic complexes [ 29 ]. Moreover, several lysosomal protein encoding genes, such as cathepsin D ( CTSD ), lysosomal-associated transmembrane protein 4A ( LAPTM4A ), tripeptidyl peptidase 1 ( TPP1 ) and damage-regulated autophagy modulator ( DRAM ), are also as p53 target genes which may contribute to the generation of autolysosomes or the degradation of autolysosomal content [ 29 , 31 , 32 ]. Recently, several studies have shown that two other p53-family members, p63 and p73 also transcriptionally regulate the autophagy program.…”
Section: Mechanisms Of Autophagymentioning
confidence: 99%
“…Therefore, the exploration of new drugs and new methods for the treatment of lung cancer requires an urgent attention. A large number of basic research and clinical practice have shown that natural products can play an important role in the tumour prevention and rehabilitation of cancer patients ( Kim et al, 2020 ; Liu et al, 2020 ; Yeh et al, 2020 ). Their reliable source and high safety are the features, which make them the main source of new drug development.…”
Section: Discussionmentioning
confidence: 99%